Importance of the ICRU bladder point dose on incidence and persistence of urinary frequency and incontinence in locally advanced cervical cancer: An EMBRACE analysis. (May 2021) - Spampinato, Sofia; Fokdal, Lars U.; Pötter, Richard; Haie-Meder, Christine; Lindegaard, Jacob C.; Schmid, Maximilian P.; Sturdza, Alina; Jürgenliemk-Schulz, Ina M.; Mahantshetty, Umesh; Segedin, Barbara; Bruheim, Kjersti; Hoskin, Peter; et al.
Highlights: Urinary side effects after radiotherapy can rely on different bladder substructures. EMBRACE I provides prospective morbidity data to study individual urinary symptoms. Frequency and incontinence are frequent side effects in cervix cancer radiotherapy. Limited clinical evidence supports the predictive value of ICRU Bladder point dose. This analysis showed correlation of ICRU Bladder point dose with incontinence. Abstract: Purpose: To identify patient- and treatment-related risk factors and dose-effects for urinary frequency and incontinence in locally advanced cervical cancer (LACC) treated with radio(chemo)therapy and image-guided adaptive brachytherapy (IGABT). Material and methods: Physician-assessed (CTCAE) and patient-reported (EORTC) frequency and incontinence recorded in the EMBRACE-I study were analysed. Risk factors analysis was performed in patients without bladder infiltration and with baseline morbidity available. Cox regression was used for CTCAE grade (G) ≥ 3 and G ≥ 2 and for EORTC "very much" and "quite a bit" or worse. Logistic regression was used for late persistent morbidity defined when CTCAE G ≥ 1 or EORTC ≥ "quite a bit" were scored in at least half of follow-ups. Results: Longitudinal data on 1153 and 884 patients were available for CTCAE and EORTC analysis, respectively. Median follow-up was 48[3-120] months. Crude incidence rates of G≥2 were 13% and 11% for frequency and incontinence, respectively. Baseline morbidity and overweight-obesity were risk factors for both symptoms. Elderly patients were at higher risk for incontinence. Patients receiving conformal-radiotherapy were at higher risk for frequency. ICRU bladder point (ICRU-BP) dose was a stronger predictor for incontinence than bladder D2cm3 . The 5-year actuarial estimate of G ≥ 2 incontinence increased from 11% to 20% with ICRU-BP doses > 75 Gy compared to ≤ 65 Gy. Frequency showed weaker associations with dose. Conclusion: ICRU-BP dose, in addition to clinical parameters, is a risk factor for urinary incontinence and shows a dose–effect after radio(chemo)therapy and IGABT. ICRU-BP dose should be monitored during treatment planning alongside volumetric parameters. Frequency seems associated with larger irradiated volumes.